Exudates of dominant plants regulate rhizospheric soil total and available heavy metals and facilitates natural restoration succession in an abandoned metal mining area - Yu, Xiaoya; Li, Ting; Wu, Xiaoni; Liu, Chang’e; Li, Shiyu; Peng, Shuxian; Wang, Sichen; Zhao, Luoqi; Duan, Changqun (Frontiers in Environmental Science, 2025)
Soil degradation caused by activities such as mining is a severe global environmental issue that drastically disrupts ecosystems. Utilizing plants and their root secretions for ecological remediation is a crucial pathway to restoring these damaged lands. The factors and mechanisms by which plant exudates in mining wastelands drive successional processes in mining areas remain largely unknown. To investigate the plant community succession over time during natural remediation and elucidate how their rhizosphere processes influence the speciation and bioavailability of soil heavy metals. The space-time substitution sampling method was used to continuously monitor the research areas at six different restoration stages of the abandoned Huize Pb–Zn mine site. Additionally, the effects of restoring plants on the total contents and speciation of soil heavy metals (Pb, Cd, Mn, Zn, Cu, Fe) were compared. The results showed that there were 31 dominant plants from 17 families, a shift from herbs to shrubs to evergreen trees. Specifically, the rhizosphere soil exhibited a significantly higher clay content compared to the non-rhizosphere soil. Furthermore, β-glucosidase played a crucial dual role: it contributed to the reduction of total heavy metal content while simultaneously enhancing metal bioavailability. Artemisia argyi Levl. et Van, Populus davidiana Dode, and Pteris vittata L. exhibit different distribution strategies for heavy metals. Artemisia argyi Levl. Populus davidiana Dode primarily transfers and accumulates heavy metals in its leaves, demonstrating its potential for phytoremediation via phytoextraction. In contrast, P. vittata predominantly sequesters heavy metals in its roots, characterizing it as a typical root accumulator or stabilizing plant. Collectively, this research reveals that natural plant succession, driven by key rhizosphere processes like enzyme activity, is an effective driver of ecological restoration in mining wastelands. The distinct heavy metal allocation strategies observed among the dominant species not only elucidate the mechanisms behind this remediation but also provide a scientific basis for selecting and combining plants for targeted phytoremediation.